Plastome Phylogenomic and Biogeographical Study on Thuja (Cupressaceae) - Adelalu, Kole F. (Biomed Res Int, 2020)
Investigating the biogeographical disjunction of East Asian and North American flora is key to understanding the formation and dynamics of biodiversity in the Northern Hemisphere. The small Cupressaceae genus Thuja, comprising five species, exhibits a typical disjunct distribution in East Asia and North America. Owing to obscure relationships, the biogeographical history of the genus remains controversial. Here, complete plastomes were employed to investigate the plastome evolution, phylogenetic relationships, and biogeographic history of Thuja. All plastomes of Thuja share the same gene content arranged in the same order. The loss of an IR was evident in all Thuja plastomes, and the B-arrangement as previously recognized was detected. Phylogenomic analyses resolved two sister pairs, T. standishii-T. koraiensis and T. occidentalis-T. sutchuenensis, with T. plicata sister to T. occidentalis-T. sutchuenensis. Molecular dating and biogeographic results suggest the diversification of Thuja occurred in the Middle Miocene, and the ancestral area of extant species was located in northern East Asia. Incorporating the fossil record, we inferred that Thuja likely originated from the high-latitude areas of North America in the Paleocene with a second diversification center in northern East Asia. The current geographical distribution of Thuja was likely shaped by dispersal events attributed to the Bering Land Bridge in the Miocene and subsequent vicariance events accompanying climate cooling. The potential effect of extinction may have profound influence on the biogeographical history of Thuja.